The solution of the equation x 4 − 4 x 2 + 3 = 0 . The solution of the equation is x = ± 3 , ± 1 . Calculation: Consider the provided equation, x 4 − 4 x 2 + 3 = 0 Put x 2 = u and convert this equation into the quadratic form, u 2 − 4 u + 3 = 0 Now, factorize the above equation, u − 3 u − 1 = 0 Put the first factor equal to zero, then replace u with x 2 and solve for x , u − 3 = 0 u = 3 x 2 = 3 x = ± 3 Put the second factor equal to zero, then replace u with x 2 and solve for x , u − 1 = 0 u = 1 x 2 = 1 x = ± 1 Check: Put x = ± 3 , ± 1 in the equation, First, put x = 3 , 3 4 − 4 3 2 + 3 = ? 0 9 − 12 + 3 = ? 0 12 − 12 = ? 0 0 = 0 Which is true. Now, put x = − 3 , − 3 4 − 4 − 3 2 + 3 = ? 0 9 − 12 + 3 = ? 0 12 − 12 = ? 0 0 = 0 Which is true. Now, put x = 1 , 1 4 − 4 1 2 + 3 = ? 0 1 − 4 + 3 = ? 0 4 − 4 = ? 0 0 = 0 Which is true. Now, put x = − 1 , − 1 4 − 4 − 1 2 + 3 = ? 0 1 − 4 + 3 = ? 0 4 − 4 = ? 0 0 = 0 Which is true. Hence, the solution of equation is x = ± 3 , ± 1 .
The solution of the equation x 4 − 4 x 2 + 3 = 0 . The solution of the equation is x = ± 3 , ± 1 . Calculation: Consider the provided equation, x 4 − 4 x 2 + 3 = 0 Put x 2 = u and convert this equation into the quadratic form, u 2 − 4 u + 3 = 0 Now, factorize the above equation, u − 3 u − 1 = 0 Put the first factor equal to zero, then replace u with x 2 and solve for x , u − 3 = 0 u = 3 x 2 = 3 x = ± 3 Put the second factor equal to zero, then replace u with x 2 and solve for x , u − 1 = 0 u = 1 x 2 = 1 x = ± 1 Check: Put x = ± 3 , ± 1 in the equation, First, put x = 3 , 3 4 − 4 3 2 + 3 = ? 0 9 − 12 + 3 = ? 0 12 − 12 = ? 0 0 = 0 Which is true. Now, put x = − 3 , − 3 4 − 4 − 3 2 + 3 = ? 0 9 − 12 + 3 = ? 0 12 − 12 = ? 0 0 = 0 Which is true. Now, put x = 1 , 1 4 − 4 1 2 + 3 = ? 0 1 − 4 + 3 = ? 0 4 − 4 = ? 0 0 = 0 Which is true. Now, put x = − 1 , − 1 4 − 4 − 1 2 + 3 = ? 0 1 − 4 + 3 = ? 0 4 − 4 = ? 0 0 = 0 Which is true. Hence, the solution of equation is x = ± 3 , ± 1 .
Solution Summary: The author explains how to calculate the solution of the equation x4-sqrt3,pm 1.
Solve the system of equation for y using Cramer's rule. Hint: The
determinant of the coefficient matrix is -23.
-
5x + y − z = −7
2x-y-2z = 6
3x+2z-7
eric
pez
Xte
in
z=
Therefore, we have
(x, y, z)=(3.0000,
83.6.1 Exercise
Gauss-Seidel iteration with
Start with (x, y, z) = (0, 0, 0). Use the convergent Jacobi i
Tol=10 to solve the following systems:
1.
5x-y+z = 10
2x-8y-z=11
-x+y+4z=3
iteration (x
Assi 2
Assi 3.
4.
x-5y-z=-8
4x-y- z=13
2x - y-6z=-2
4x y + z = 7
4x-8y + z = -21
-2x+ y +5z = 15
4x + y - z=13
2x - y-6z=-2
x-5y- z=-8
realme Shot on realme C30
2025.01.31 22:35
f
Use Pascal's triangle to expand the binomial
(6m+2)^2
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, algebra and related others by exploring similar questions and additional content below.
Interpreting Graphs of Quadratic Equations (GMAT/GRE/CAT/Bank PO/SSC CGL) | Don't Memorise; Author: Don't Memorise;https://www.youtube.com/watch?v=BHgewRcuoRM;License: Standard YouTube License, CC-BY
Solve a Trig Equation in Quadratic Form Using the Quadratic Formula (Cosine, 4 Solutions); Author: Mathispower4u;https://www.youtube.com/watch?v=N6jw_i74AVQ;License: Standard YouTube License, CC-BY